THE FOSSIL RECORD OF CAMELIDS (MAMMALIA, CETARTIODACTYLA) IN TUCUMÁN PROVINCE, NORTHWESTERN ARGENTINA (Ameghiniana, 2021)
The presence of fossil camelids in Tucumán, northwestern Argentina, has been recognized for many years but its relevance has not been fully evaluated so far. Here, we review previous mentions of fossil camelids for this province, present new material, and compare it with fossil and extant specimens of South American camelids, clarifying its taxonomic context and discussing its paleobiogeographic significance. For Tucumán we recognize Vicugna vicugna (Tafí del Valle Formation, late Pleistocene–early Holocene) and Palaeolama sp. (Tucumán Formation, late Pleistocene), mainly based on size and dental features. The current distribution of V. vicugna is restricted to the Central Andes, in the Puna and High Andean environments over 3200 m altitude; there is no mention, neither current nor historical, for Tucumán. Its presence at around 2200 m in the Tafí valley during the Quaternary indicates cooler and drier conditions than those currently established. The observations made in the context of this contribution allow us to establish that the species V. provicugna is a synonym of V. vicugna. In turn, we consider that the validity of the species Palaeolama hoffstetteri, only based on postcranial remains, should be properly evaluated in the future.